3D TOF-PET image reconstruction using total variation regularization. (December 2020) - Raczyński, L.; Wiślicki, W.; Klimaszewski, K.; Krzemień, W.; Kopka, P.; Kowalski, P.; Shopa, R.Y.; Bała, M.; Chhokar, J.; Curceanu, C.; Czerwiński, E.; Dulski, K.; et al.
Highlights: TV regularization in image space is more efficient than usual iterative approaches. The efficiency of proposed method comes from the one-time TOF backprojection step. The overall operator can be modelled with a closed-form analytical formula. The operator models TOF uncertainty and spatial detection uncertainty inside detector. Abstract: In this paper we introduce a semi-analytic algorithm for 3-dimensional image reconstruction for positron emission tomography (PET). The method consists of the back-projection of the acquired data into the most likely image voxel according to time-of-flight (TOF) information, followed by the filtering step in the image space using an iterative optimization algorithm with a total variation (TV) regularization. TV regularization in image space is more computationally efficient than usual iterative optimization methods for PET reconstruction with full system matrix that use TV regularization. The efficiency comes from the one-time TOF back-projection step that might also be described as a reformatting of the acquired data. An important aspect of our work concerns the evaluation of the filter operator of the linear transform mapping an original radioactive tracer distribution into the TOF back-projected image. We obtain concise, closed-form analytical formula for the filter operator. The proposed method is validated with the Monte Carlo simulations of the NEMA IEC phantom using a one-layer, 50 cm-long cylindrical device called Jagiellonian PET scanner. The results show a better image quality compared with the reference TOF maximum likelihood expectation maximization algorithm.